Antioxidant status in neonatal jaundice before and after phototherapy - S Ayyappan; Sachu Philip; N Bharathy; V Ramesh; C Naveen Kumar; S Swathi; A Arun Kumar (Wolters Kluwer Medknow Publications, 2015)
Background: Neonatal jaundice refers to yellow coloration of the skin and the sclera (whites of the eyes) of newborn babies that result from the accumulation of bilirubin in the skin and mucous membranes. Because bilirubin is potentially toxic to the central nervous system. Genetic disorders of bilirubin conjugation, particularly the common Gilbert's syndrome, can also contribute to neonatal hyperbilirubinemia. Objective: The aim of this study was to evaluate the lipid per-oxidation and antioxidant enzyme activities in patients with neonatal jaundice before and after phototherapy. Materials and Methods: The study includes 50 neonatal jaundice patients with average age 2-15 days. All patients of neonatal jaundice receiving phototherapy except feeding, cleaning. Subjects selected were from the patients attending Pediatrics Department. Plasma malondialdehyde (MDA), erythrocyte glutathione peroxidase (GPX), superoxide dismutase and catalase (CAT) to monitor the bilirubin level. Results: The results show increased levels of bilirubin compared with controls (P < 0.001) shows the level of plasma MDA in control, before and after phototherapy. Represents the level of GPX was significantly increased in after the phototherapy group when compared with before phototherapy and control SPSS soft ware: (P < 0.001). Shows the reduced glutathione (GSH) level in plasma was significantly decreased in the after phototherapy group when compared with before phototherapy and control (P < 0.001). And finally with ascorbic acid and CAT. Conclusion: It is evident from the study that increased oxidative stress in neonatal jaundice babies leads to decrease in the levels of antioxidants like GSH and ascorbic acid and disturb their metabolism, that weaken their ability to fight the growing stress. Intense oxidative stress and decreased antioxidants may contribute to neural cell death and alter the erythrocytomembrane structure processing in neonatal jaundice.